2020
DOI: 10.26434/chemrxiv.12062685.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimal Dissociation Methods Differ for N- and O-glycopeptides

Abstract: <p><a>Site-specific characterization of glycosylation requires intact glycopeptide analysis, and recent efforts have focused on how to best interrogate glycopeptides using tandem mass spectrometry (MS/MS). Beam-type collisional activation, i.e., higher-energy collisional dissociation (HCD), has been a valuable approach, but stepped collision energy HCD (sceHCD) and electron transfer dissociation with HCD supplemental activation (EThcD) have emerged as potentially more suitable alternatives. Both sc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 151 publications
(175 reference statements)
0
3
0
Order By: Relevance
“…In a study of tryptic glycopeptides enriched with wheat germ agglutinin from human urine using this ionization method, Darula et al ( 2019) identified new O-acetyl-sialic acid (Neu5,9Ac 2 , 195) on the galactose residues of core-1 (196), and core-2 (197) O-glycans. , Malaker, Driessen, et al (2020) have compared the advantages and disadvantages of conventional HCD, stepped collision energy (sceHCD), ETD, and electron transfer dissociation with HCD supplemental activation (EThcD) for the analysis of intact N-and O-glycopeptides. For N-glycopeptides, HCD and sceHCD generated similar numbers of identifications, although sceHCD generally provided higher quality spectra.…”
Section: Electron-transfer Dissociation (Etd)mentioning
confidence: 99%
“…In a study of tryptic glycopeptides enriched with wheat germ agglutinin from human urine using this ionization method, Darula et al ( 2019) identified new O-acetyl-sialic acid (Neu5,9Ac 2 , 195) on the galactose residues of core-1 (196), and core-2 (197) O-glycans. , Malaker, Driessen, et al (2020) have compared the advantages and disadvantages of conventional HCD, stepped collision energy (sceHCD), ETD, and electron transfer dissociation with HCD supplemental activation (EThcD) for the analysis of intact N-and O-glycopeptides. For N-glycopeptides, HCD and sceHCD generated similar numbers of identifications, although sceHCD generally provided higher quality spectra.…”
Section: Electron-transfer Dissociation (Etd)mentioning
confidence: 99%
“…Other software tools that take glycan fragmentation into account can benefit from collision energy stepping. [24][25]33 We therefore provide the optimized instrument method both with and without TIMS stepping in the ProteomeXchange repository under the identifier PXD047898. Data was visualized using Python 3.10.10 with the packages Matplotlib 3.7.1, Scipy 1.10.1, Numpy 1.24.3 and Pandas 1.5.3.…”
Section: Data Interpretationmentioning
confidence: 99%
“…Potential solutions are the use of advanced fragmentation techniques like electron-based dissociation (ExD), that produce c-and z-type peptide fragment ions while retaining the intact glycan moiety. [25][26] However, these techniques are not widely available. More commonly used CID instruments can overcome this obstacle by using higher collision energies to increase the yield of peptide fragment ions or performing CID stepping to fragment the glycan moiety at lower collision energies and the peptide moiety at high collision energies.…”
Section: Introductionmentioning
confidence: 99%